A liquid calcium+vitamin D3 supplement is effective prophylaxis against hypocalcemic toxicity during apheresis platelet donation. Issue 1 (27th June 2017) - Weinstein, Robert; Haynes, Stefanie; Zhao, Yong; Hickson, Elda; Linden, Jeanne; St. Pierre, Patricia; Ducharme, Paula; Sulmasy, Paula; Graves, Molly; Bailey, Jeffrey A.; Welch, Linda; Simard, Amie; et al.
Abstract: Hypocalcemic toxicity, because of return of citrate anion to the donor, is the major toxicity of apheresis platelet donation. Oral calcium carbonate, given prophylactically at the start of donation, has shown limited ability to alleviate this toxicity. We examined whether repeated prophylactic doses of calcium carbonate, or of a liquid preparation containing calcium citrate, calcium phosphate, and vitamin D3, would be more effective at preventing symptoms of hypocalcemic toxicity. Symptoms were reported by 48% of donors who received no prophylaxis and 60% of donors who received 1000 mg of oral calcium carbonate at the start of, and every 20 minutes during, donation ( P = 0.711). Only 19.2% of donors who received the liquid preparation (1000 mg calcium, 1000 IU vitamin D3 ) reported symptoms ( P = 0.040 versus no prophylaxis, P = 0.039 versus calcium carbonate). This difference was not because of gender, weight, age, or blood volume of the donor. Neither calcium preparation prevented a measurable fall in plasma ionized calcium during donation. We conclude that liquid calcium citrate/calcium phosphate/vitamin D3 provides effective prophylaxis against hypocalcemic toxicity during platelet donation, however it does not prevent a fall in plasma ionized calcium.